2009
DOI: 10.1111/j.1528-1167.2008.01998.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and surgical outcomes for mild type I and severe type II cortical dysplasia: A critical review and the UCLA experience

Abstract: Summary Recent findings on the clinical, electroencephalography (EEG), neuroimaging, and surgical outcomes are reviewed comparing patients with Palmini type I (mild) and type II (severe) cortical dysplasia. Resources include peer‐reviewed studies on surgically treated patients and a subanalysis of the 2004 International League Against Epilepsy (ILAE) Survey of Pediatric Epilepsy Surgery. These sources were supplemented with data from University of California, Los Angeles (UCLA). Cortical dysplasia is the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

29
296
7
50

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 352 publications
(382 citation statements)
references
References 127 publications
(241 reference statements)
29
296
7
50
Order By: Relevance
“…Other authors 15 reached similar results when they showed that after complete resection, 80% of patients are seizure free compared with 20% with incomplete resections. Compared with Type I, patients with FCD Type II present at younger ages, have higher seizure frequencies, and are extratemporal.…”
Section: Malformations Due To Abnormal Neuronal and Glial Proliferatisupporting
confidence: 65%
“…Other authors 15 reached similar results when they showed that after complete resection, 80% of patients are seizure free compared with 20% with incomplete resections. Compared with Type I, patients with FCD Type II present at younger ages, have higher seizure frequencies, and are extratemporal.…”
Section: Malformations Due To Abnormal Neuronal and Glial Proliferatisupporting
confidence: 65%
“…4 Using these classification systems, differences in clinical behavior, imaging appearance, and outcomes have been identified among CD subtypes. 4,19 These findings have significant implications for improving/developing diagnostic techniques to assist in patient selection for surgical therapy. Multiple dysplasia types in one patient have been rarely described, 9 but may not be evident, unless spatially distant resections are performed, and pathologically analyzed.…”
mentioning
confidence: 99%
“…As mentioned by other authors [5,6,22,26], FCD is associated with a wide range of clinical presentations. There is no particular seizure semiology that characterizes patients with FCD compared with other surgical series of epilepsy patients [16][17][18]. There are no distinctive interictal or ictal scalp EEG features that are exclusively associated with FCD.…”
Section: Discussionmentioning
confidence: 94%
“…One possible explanation for these findings, including the two free seizure patients, may be a different selection criterion, since most of the published series are surgical [16,17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation